2013
DOI: 10.1111/add.12093
|View full text |Cite
|
Sign up to set email alerts
|

A randomized study of cellphone technology to reinforce alcohol abstinence in the natural environment

Abstract: Aims Contingency management (CM) uses tangible incentives to systematically reinforce abstinence and is among the most efficacious psychosocial substance abuse treatments. This study assessed the feasibility and initial efficacy of a portable CM procedure designed to address technical limitations for detecting drinking that have prevented using CM for alcohol problems. Design Participants received a cell phone, breathalyzer, and training on video-recording alcohol breath tests (BrACs) and texting results. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
141
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(151 citation statements)
references
References 26 publications
9
141
0
1
Order By: Relevance
“…Contingency management, a technique in which a target behavior (here, abstinence) is reinforced with vouchers or the opportunity to win money prizes, is highly effective (e.g., Dutra et al 2008). Indeed, behavior analysis has techniques available to reduce harmful behaviors including substance abuse (Alessi and Petry 2013;Andrade et al 2012), medication noncompliance (e.g., Petry et al 2015), and self-injurious behavior (e.g., Hanley et al 1998). As part of our ethical underpinnings, behavior analysts require the use of effective interventions (cf.…”
Section: Behavior Analysis and Moralitymentioning
confidence: 99%
“…Contingency management, a technique in which a target behavior (here, abstinence) is reinforced with vouchers or the opportunity to win money prizes, is highly effective (e.g., Dutra et al 2008). Indeed, behavior analysis has techniques available to reduce harmful behaviors including substance abuse (Alessi and Petry 2013;Andrade et al 2012), medication noncompliance (e.g., Petry et al 2015), and self-injurious behavior (e.g., Hanley et al 1998). As part of our ethical underpinnings, behavior analysts require the use of effective interventions (cf.…”
Section: Behavior Analysis and Moralitymentioning
confidence: 99%
“…
Alessi & Petry [1] examined if cellular phone technology could be used to provide contingency management (CM)-based reinforcement for alcohol abstinence by comparing two randomized conditions: (1) CM for submitting videorecorded alcohol breath tests (BrAC) via cellular phones regardless of the results and (2) the same condition plus escalating vouchers for negative alcohol breaths (n-BrAC). They found that the percentage of n-BrAC and the longest duration of consecutive n-BrAC were greater in the group that received CM for alcohol abstinence.
…”
mentioning
confidence: 99%
“…The cost of a cellular phone plan per month per phone for 200 minutes of talk, restricted to study numbers and unlimited texting, was $27. The relative affordability of cellular phone packages can reduce the financial and time constraints experienced by the participants and staff and will ultimately be cost-effective in the long term.Alessi & Petry [1] are the first to use cellular phone technology to deliver CM for alcohol abstinence, and their study may serve as a model for other researchers to combine rigorous methodology, theory and modern technology to narrow the research-to-practice gap. Future studies should assess whether CM procedures using cellular phones can yield outcomes greater the standard CM procedures, and whether it can be used to reach a variety of populations.…”
mentioning
confidence: 99%
See 2 more Smart Citations